2017
DOI: 10.1126/scitranslmed.aah5645
|View full text |Cite
|
Sign up to set email alerts
|

Drug discovery for Diamond-Blackfan anemia using reprogrammed hematopoietic progenitors

Abstract: Diamond-Blackfan anemia (DBA) is a congenital disorder characterized by the failure of erythroid progenitor differentiation, severely curtailing red blood cell production. Because many DBA patients fail to respond to corticosteroid therapy, there is considerable need for therapeutics for this disorder. Identifying therapeutics for DBA requires circumventing the paucity of primary patient blood stem and progenitor cells. To this end, we adopted a reprogramming strategy to generate expandable hematopoietic proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
88
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 45 publications
3
88
0
Order By: Relevance
“…Patient-derived iPSCs have been used to model various diseases, including long QT syndrome (LQTS) [159, 160], alpha-1 antitrypsin (AAT) deficiency [161, 162], familial dysautonomia (FD) [163, 164] Diamond-Blackfan anemia (DBA) [165167], familial Alzheimer’s disease [168] and RASopathy disorders [169, 170], to name a few. Successful disease modeling not only sheds light on disease mechanisms but also leads to the development of in vitro assays – readouts of disease-associated phenotype – that facilitate high-throughput drug screening.…”
Section: Translating Lfs Ipsc Models Into Clinical Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-derived iPSCs have been used to model various diseases, including long QT syndrome (LQTS) [159, 160], alpha-1 antitrypsin (AAT) deficiency [161, 162], familial dysautonomia (FD) [163, 164] Diamond-Blackfan anemia (DBA) [165167], familial Alzheimer’s disease [168] and RASopathy disorders [169, 170], to name a few. Successful disease modeling not only sheds light on disease mechanisms but also leads to the development of in vitro assays – readouts of disease-associated phenotype – that facilitate high-throughput drug screening.…”
Section: Translating Lfs Ipsc Models Into Clinical Therapiesmentioning
confidence: 99%
“…Another recent study also utilized iPSC-derived hematopoietic progenitors to perform a non-biased drug screening for DBA, which identified autophagy as a therapeutic pathway in this rare blood disorder. iPSC-based drug screening has also been applied to diseases other than genetic disorders, such as infectious diseases [167]. iPSC-derived hepatocytes have been used to screen drugs for treating chronic infectious disease, such as hepatitis B and liver-stage malaria [172, 173].…”
Section: Translating Lfs Ipsc Models Into Clinical Therapiesmentioning
confidence: 99%
“…These findings suggest that the DBA iPSC model might help explore the pathological role of dysregulation of ribosome biosynthesis in developing anemia [109]. The same conclusion was also made by another study using distinct DBA patient iPSCs harboring either RPS19 (R94X) or RPL5 (Y16X) [108]. Here, an unbiased chemical screen was performed on DBA iPSC-derived hematopoietic progenitors and the autophagy inducer SMER28 was identified as a potential compound that might enhance erythropoiesis and ameliorate the defect in erythroid differentiation [108].…”
Section: Current Advances In Osteosarcoma Biology Using Ipsc Modelsmentioning
confidence: 57%
“…Numerous laboratories have demonstrated that PSCs (ESCs and iPSCs, Box 6) overcome many limitations of other model systems and can serve as a relevant model system to study the etiologies of cancer including osteosarcoma (in LFS [10], WS [106, 107], DBA[108, 109] and RB [110]) (Figure 3B), brain tumors [111, 112], and leukemia [113]. …”
Section: Current Advances In Osteosarcoma Biology Using Ipsc Modelsmentioning
confidence: 99%
“…The involvement of HSP70 in DBA pathophysiology adds additional complexity to the various mechanisms thought to play a role in DBA pathophysiology, which include (1) the ribosome maturation defect, 12 resulting in the p53 stabilization responsible for cell cycle arrest and increased apoptosis leading at least in part to the erythroblastopenia 37,54 ; (2) the selective translation defect of specific transcripts such GATA1 31 and BAG1, CSDE1 51 ; (3) the autophagy 58,59 ; and (4) the imbalance between decreased globin synthesis and free heme excess (L.D.C., DBA foundation consensus conference, 6 March 2016, and Yang et al 60 ), which generates reactive oxygen species and subsequent increase in cell toxicity and apoptosis of erythroid progenitors and precursors. The balance between each of mechanisms and perhaps others need to be further deciphered to account for the variable and heterogeneous severity of the disease phenotype.…”
mentioning
confidence: 99%